Changes in the regulatory policy in higher education of Ecuador during the last years - Urgilés Urgilés, Gladys Primavera; Chávez Urgilés, Karen Aracely (SATHIRI, 2019)
Regulatory policy is a technical tool that governments can use to apply regulatory controls to achieve the objectives that have been set for their management. In the country, strong changes were made to the regulatory policies since 2008 when the Constitution of the Republic of Ecuador was updated, and as a result of this modification, higher education has had a strong impact in recent years. To analyze the effects of regulatory policy in higher education, statistical data, comments of experts regarding the main changes and figures published by the National Secretary of Higher Education, Science, Technology and Innovation (SENESCYT), as of the year were reviewed. 2006 to the present. The modifications to the regulatory policy have impacted on the generation of entities of control and supervision, university evaluation, closure of entities that did not comply with the basic quality, entrance examination for universities, among others, whose main objective was to comply with two guidelines clearly stipulated in the Constitution of the Republic, such as ensuring the quality of higher education institutions, and ensuring that there is free offer. The figures analyzed allowed to verify a notable improvement in terms of public investment for higher education, annual items assigned to scholarships, participation of universities and students in research, among others.